1999
DOI: 10.1029/1999gl900507
|View full text |Cite
|
Sign up to set email alerts
|

Role of planetary waves in the stratosphere‐troposphere coupled variability in the northern hemisphere winter

Abstract: Abstract. The role of planetary waves in stratospheretroposphere coupled variability is investigated using an extended singular value decomposition analysis of zonalmean zonal wind and the vertical component of the EliassenPalm (E-P) flux for the winters from 1979/80 to 1995/96. The results suggest a close relationship between anomalies of zonal-mean zonal wind and the convergence zone of E-P flux, which together shift poleward and downward from the stratosphere to the troposphere as time advances. Following e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
111
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 126 publications
(125 citation statements)
references
References 15 publications
14
111
0
Order By: Relevance
“…The same dataset is used as that in the previous study [Kuroda and Kodera, 1999]: National Centers for Environmental Prediction (NCEP) operational data combined with the stratospheric data derived from satellite observations [Randel, 1992]. Pentad (five-day) mean data for 18 years (1979 to 1996) covering pressure levels from 850 to i hPa are first created as a basic dataset.…”
Section: Data and Methods Of Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…The same dataset is used as that in the previous study [Kuroda and Kodera, 1999]: National Centers for Environmental Prediction (NCEP) operational data combined with the stratospheric data derived from satellite observations [Randel, 1992]. Pentad (five-day) mean data for 18 years (1979 to 1996) covering pressure levels from 850 to i hPa are first created as a basic dataset.…”
Section: Data and Methods Of Analysismentioning
confidence: 99%
“…Thompson and Wallace [1998] considered that the AO extends from the troposphere up into the stratosphere during the winter-spring season. However, recent analysis [Kuroda and Kodera, 1999] indicates that changes in stratospheric zonal wind anomalies first appear in the subtropics and slowly propagate poleward and downward into the troposphere. Similar downward penetration of circulation anomalies related to the AO is also found in the analysis by Baldwin and Dunkerton [1999].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the three positive centres between 40 • N and 60 • N are nearly collocated. Based on the later study, it could arguably be understood as a downward influence of the enhanced positive phase of the northern annular mode, or NAM (Baldwin and Dunkerton, 1999;Kuroda and Kodera, 1999), associated with the cold polar stratosphere. In the stratosphere (50 mb), the anomalies show clear evidence of a strengthened polar vortex, maximizing at lag 0, and fading at lag +1.…”
Section: The 500 Mb Tropospheric Circulation During Cold Stratospherimentioning
confidence: 99%
“…However, studies in the recent decades have revealed that stratosphere can play an important role in the near surface climate change. For example, data diagnosis showed that the stratosphere zonal-mean zonal wind anomalies can propagate poleward and downward to the troposphere consecutively from the stratopause region (Christiansen 2001;Kodera 1995;Kuroda and Kodera 1999). It was further illustrated that the anomalous Arctic Oscillation (AO) signal, which is the dominant mode of the geopotential fields north of 20°N, appears firstly in the upper stratosphere, and propagates all the way down to the troposphere and can have significant influence on the surface extended-range weather and shortterm climate Dunkerton, 1999, 2001;Baldwin et al, 2003b;Moritz et al, 2002).…”
Section: Introductionmentioning
confidence: 99%